UNDERSTANDING BARRIERS TO DESIGN THINKING ADOPTION IN INDIAN MANUFACTURING MSMES: EVIDENCE FROM A SEQUENTIAL MIXED-METHODS STUDY - Idrisi, Meraj Alam; Singari, Ranganath M. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The formulation of Human centred Innovation, Design Thinking (DT) is gaining traction as a key methodology for innovation, but its implementation within the Indian manufacturing Micro, Small, and Medium Enterprise (MSME) sector, which contributes about 45% of the manufacturing output in the country, is limited and patchy. In this paper, the multi-level barriers for DT adoption in Indian manufacturing MSMEs are empirically identified and quantified, and the barriers are theorised. A sequential explanatory mixed-methods design was employed: a 47-item structured survey of 312 MSMEs across five major industrial clusters was followed by 28 in-depth interviews. Exploratory and Confirmatory Factor Analysis identified seven barrier dimensions explaining 68.4% of variance. Covariance-based Structural Equation Modelling (n = 312; CFI = 0.94; RMSEA = 0.063; R² = 0.58) supported all seven hypotheses. Financial Constraints (β = −0.41) and Awareness Deficit (β = −0.38) emerged as the strongest inhibitors, while Policy Ecosystem quality positively moderated the readiness–adoption pathway (β = +0.31). Qualitative themes-the “design blindspot,” the “thin-margin trap,” and the policy “last-mile” gap-explain the cognitive, financial, and institutional mechanisms underlying these effects. The study contributes (a) the first statistically validated barrier taxonomy for DT adoption in Indian manufacturing MSMEs, (b) a three-tier (micro–meso–macro) Layered Barrier Model integrating four theoretical lenses (Diffusion of Innovations, TAM, RBV, Institutional Theory), and (c) a five-stage adoption roadmap with a matching policy-intervention matrix for emerging-economy SME ecosystems.